Measuring the Impact of Product Mix Heterogeneity on Manufacturing Overhead Cost - Anderson, Shannon W. (The Accounting Review, 1995)
[This paper examines the impact of product mix heterogeneity (PMH) on manufacturing overhead costs (MOHC) in three plants of a textile firm. An approach for measuring PMH is adapted from the group technology literature of operations. Factor analysis of product engineering specifications identifies seven forms of PMH for woven fabrics. Regression analysis indicates that two of the seven forms of heterogeneity are costly: differences in processing efficiency and in customer-specified quality requirements. The new measures of PMH perform better in estimating MOHC than the traditional measure of PMH, the number of products produced. Finally, the paper provides evidence that experience producing a heterogeneous mix of products mitigates costs of PMH.]